Job satisfaction and firm leverage: Evidence from the "China's Best Employer Award 100" winners - Hongmei Xu; Xiaoran Ni; Chuntao Li; Yanan Liu (China Journal of Accounting Research, 2020)
In this study, we examine the relationship between job satisfaction and firm leverage using a sample of Chinese listed firms. We find that in a sample of "China's 100 Best Employers Award" winners during 2011-2017, job satisfaction is negatively associated with firm leverage. The effect is more pronounced in firms with higher distress risk and operating in human capital intensive industries. We confirm the validity of the main findings using a matched sample and a series of robustness checks. Overall, our results indicate that firms can credibly demonstrate their commitment to stakeholders and re-shape their capital structure by improving job satisfaction.
Keywords: 650; Best employers; Firm leverage; Job satisfaction; Stakeholder